Performing Japan : Contemporary Expressions of Cultural Identity. - Johnson, Henry (BRILL, 2008)
Using an interdisciplinary, theoretical and ethnographic approach, editors have brought together a rich collection of current research on contemporary Japanese performance practices. Topics covered include theatre, music, art, fashion and technology, media, architecture and tourism.